The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s13568-020-01136-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a novel bacterium, Pseudomonas sp. ZyL-01, involved in the biodegradation of CL-20

Abstract: Hexanitrohexaazaisowurtzitane (CL-20) is a compound with a polycyclic cage and an N-nitro group that has been shown to play an unfavorable role in environmental fate, biosafety, and physical health. The aim of this study was to isolate the microbial community and to identify a single microbial strain that can degrade CL-20 with desirable efficiency. Metagenomic sequencing methods were performed to investigate the dynamic changes in the composition of the community diversity. The most varied genus among the mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Among them, CL-20 (1) is the most wellknown representative and extensive studies have confirmed its xenobiotic nature (Figure 1). Toxicology studies investigating the effects of high doses of CL-20 on animal organisms have revealed that its negative impact, mediated through various biotransformation pathways, is mostly reversible [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, current genetic research methods demonstrate the reversibility of the neurotoxic effects of compound 1 on Eisenia fetida [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, CL-20 (1) is the most wellknown representative and extensive studies have confirmed its xenobiotic nature (Figure 1). Toxicology studies investigating the effects of high doses of CL-20 on animal organisms have revealed that its negative impact, mediated through various biotransformation pathways, is mostly reversible [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, current genetic research methods demonstrate the reversibility of the neurotoxic effects of compound 1 on Eisenia fetida [11].…”
Section: Introductionmentioning
confidence: 99%